Management recommendations for invasive alien plants in a university arboretum of North Sumatra, Indonesia - AGNES JOSEPHINE AYUNINGTYAS; SURATNI AFRIANTI; SHIGEYUKI BABA; MOHAMMAD BASYUNI (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Ayuningtyas AJ, Afrianti S, Baba S, Basyuni M. 2025. Management recommendations for invasive alien plants in a university arboretum of North Sumatra, Indonesia. Biodiversitas 26: 5544-5555. Invasive alien plants threaten biodiversity and ecosystem stability, yet studies in Indonesian arboreta remain limited. This study assessed the diversity, ecological characteristics, and management priorities of invasive alien plants in the Universitas Sumatera Utara (USU) Arboretum, North Sumatra, Indonesia. The objective of this study is threefold: first, to identify the diversity of invasive alien plants; second, to analyze their taxonomic relationships and interactions with native species; and third, to provide recommendations for effective management. A systematic nested plot design was implemented, entailing the utilization of 250 plots, each measuring 5 × 5 m, with subplots of 2 × 2 m. A total of 29 invasive species, classified into 16 families, were documented. The most prevalent species were Asystasia gangetica (1,361 individuals) and Miconia crenata (523 individuals), with a combined Importance Value Index (IVI) of 148.97%. The diversity, richness, and evenness indices were found to be moderate. The Jaccard Index ranged from 0.184 to 0.606, indicating weak interspecies similarity across plots. Three management strategies were proposed: (i) Site management for A. gangetica and M. crenata, (ii) Regular monitoring for six moderately invasive species, (iii) Limited control for 21 species of negligible risk. These findings provide a scientific basis for developing structured management and early detection systems to sustain biodiversity and ecological integrity in university arboreta and other ex-situ conservation sites.